Portable mechanical ventilation with closed-loop control of inspired fraction of oxygen maintains oxygenation in the setting of hemorrhage and lung injury - Jernigan, Peter L. (J Trauma Acute Care Surg, 2015)
BACKGROUND: Closed-loop controllers (CLCs) embedded within portable mechanical ventilators may allow for autonomous weaning. The ability of CLCs to maintain adequate oxygenation in the setting of hemorrhage and lung injury is unknown. We hypothesized that a portable ventilator with a CLC for inspired fraction of oxygen (FIO(2)) could provide oxygenation in a porcine model of hemorrhage and lung injury. METHODS: Female pigs randomized to the study group (n = 6) underwent a pressure-controlled bleed (mean arterial pressure = 40 mm Hg for 30 minutes). Acute lung injury was induced by saline lung lavage followed by intentional infliction of barotrauma. Sham pigs (n = 6) underwent placement of monitoring devices without hemorrhage or lung injury. All pigs were then placed on a portable ventilator modified with a CLC algorithm, which uses feedback from pulse oximetry (SpO(2)) and FIO(2) trends to adjust FIO(2) and maintain a target SpO(2) of 94% (2%). The initial FIO(2) was set at 0.60. Tidal volume, positive end-expiratory pressure, rate, and inspiratory-to-expiratory ratio were constant unless changes were required clinically. RESULTS: Study pigs had lower mean arterial pressures than shams at all time points except baseline. PaO(2)/FIO(2) ratios were less than 300 and significantly lower than both baseline values and corresponding sham values at all time points. The CLC weaned the FIO(2) at a reduced rate in study pigs relative to shams with a final mean FIO(2) of 0.54 and 0.29 in study and sham pigs, respectively (p < 0.05). There was a significant divergence in the study and sham FIO(2) curves but no significant difference in oxygen saturation or hypoxemia. CONCLUSION: Adequate oxygenation can be maintained in the setting of hemorrhage and lung injury using a portable ventilator embedded with a CLC of FIO(2) based on pulse oximetry. These devices may be valuable for providing advanced medical care in resource-limited environments.